Tissue Window in Stroke Thrombolysis study (TWIST): a safety study. - Hill, MD; Kenney, C; Dzialowski, I; Boulanger, J; Demchuk, A; Barber, P; Watson, T; Weir, N; Buchan, A (2013)
BACKGROUND: Stroke thrombolysis is limited by the "last-seen well" principle, which defines stroke onset time. A significant minority of stroke patients (~15%) awake with their symptoms and are by definition ineligible for thrombolysis because they were "last-seen well" at the time they went to bed implying an interval that is most often greater than three hours. METHODS: A single-centre prospective, safety study was designed to thrombolyse 20 subjects with stroke-on-awakening. Patients were eligible for inclusion if they were last seen well less than 12 hours previously, specifically including those who awoke from sleep with their stroke deficits. They had a baseline computed tomogram (CT) scan with an ASPECTS score greater than 5, no evidence of well-evolved infarction and a CT angiogram / Trans-cranial Doppler ultrasound study demonstrating an intracranial arterial occlusion. Patients fulfilled all other standard criteria for stroke thrombolysis. The primary outcome was safety defined by symptomatic ICH or death. RESULTS: Among 89 screened patients, 20 were treated with thrombolysis. Two patients (10%) died due to massive carotid territory stroke and two patients (10%) died of stroke complications. Two patients (10%) showed asymptomatic intracerebral hemorrhage (ICH) (petechial hemorrhage) and none symptomatic ICH. Reasons for exclusion were: (a) ASPECTS ≤ 5 (29); (b) well-evolved infarcts on CT (19); (c) historical mRS > 2 (17); (d) no demonstrable arterial occlusion or were too mild to warrant treatment (10). CONCLUSIONS: Patients who awake with their deficits can be safely treated with thrombolysis based upon a tissue window defined by NCCT and CTA/TCD.